Preparation of chitosan modified montmorillonite biocomposite for sonocatalysis of dyes: Parameters and degradation mechanism - Karaca, Semra; Onal, Elif Cakmak; Acisli, Ozkan; Khataee, Alireza (Elsevier Science Sa, 2021)
In this study, the natural chitosan biopolymer was immobilized onto montmorillonite (MMT) surface for efficient ultrasound-assisted removal of dyes in aqueous solution. The MMT, chitosan, and prepared chitosan/MMT samples were characterized using XRD, HR-SEM/EDX, FT-IR, and BET analyses. The sonocatalytic activity of the chitosan/MMT biocomposite was compared in degradation Acid Orange 7 (AO7), Basic Red 46 (BR4), Basic Yellow 2 (BY2) and Basic Yellow 28 (BY28). To define the optimized reaction conditions, the removal efficiency of BY2 was examined by various operational variables, such as biocomposite dosage, initial BY2 concentration, degree of high power, and pH. Besides, the effects of various treatment processes and scavengers were tested. The experimental results revealed that the highest removal efficiency, 82.74%, was obtained at natural pH of 6.95 for the processing conditions of 1.0 g/L catalyst dosage, 200 mg/L dye concentration, 350 W high power, and 60 min reaction time. Moreover, the obtained results pointed out that the sonocatalytic process was the most effective process due to the increased mass transfer and the degradation of BY2 by (OH)-O-center dot radicals generation. The kinetic of sonocatalytic process can be represented by the combination of both pseudo-second order and intra-particle diffusion models. Among the Langmuir, Freundlich, BET, Temkin, and Dubinin-Radushkevich isotherm models, the Langmuir model was found to be the best conformity. The trapping experiments suggested that the hydroxyl radicals ((OH)-O-center dot) for BY2 oxidation have a predominant role, whereas hydroperoxyl (HO2 center dot) radicals have less effect. GC-MS analysis was also used for the determination of by-products that occurred throughout the removal process.
Keywords: Ultrasound-assisted degradation; Sonocatalyst; Hydroxyl radicals; Chitosan/MMT composite